ANALISIS FAKTOR AKTIVITAS INVESTASI TERHADAP MINAT BERINVESTASI PADA MAHASISWA STIE APRIN PALEMBANG - Herlina suhercy; Tedy Setiawan Saputra; Serli Lestari; M Rizky (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2024)
Abstract This study aims to analyze the factors influencing the investment interest of students at STIE APRIN Palembang in the capital market, including expected return, self-efficacy, perceived risk, subjective norms, perceived behavior control, and investment attitudes. Using a qualitative descriptive method through interviews, the results indicate that expected return and self-efficacy have a positive influence, while perceived risk serves as the main barrier due to low financial literacy. Subjective norms and perceived behavior control are shaped by social factors and ease of access, while investment attitudes encourage student participation. The study recommends enhancing financial literacy and improving access to investment information.